2009
DOI: 10.1111/j.1365-2648.2008.04918.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poststroke quality of life in older Chinese adults

Abstract: Title. Predictors of poststroke quality of life in older Chinese adults. Aim. This paper is a report of a study to identify the changes in poststroke quality of life and other clinical issues among older Chinese adults from 1 month to 6 months after stroke and the predictors of poststroke quality of life at 6 months. Background. Stroke survivors are known to suffer from prolonged and multiple impairments leading to a compromised quality of life, but few studies report early predictors for quality of life among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
(112 reference statements)
1
6
0
Order By: Relevance
“…Stroke severity (with its strongest correlate: disability) and post‐stroke emotional well‐being (measured by negative feelings and laughter frequency) were the principal consistent determinants of physical, psycho‐emotional, cognitive, and ecosocial HRQOL after stroke. These findings are supported by many other studies involving other populations around the world . On the other hand, sense of purpose in life was the major determinant of spiritual HRQOL after stroke.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Stroke severity (with its strongest correlate: disability) and post‐stroke emotional well‐being (measured by negative feelings and laughter frequency) were the principal consistent determinants of physical, psycho‐emotional, cognitive, and ecosocial HRQOL after stroke. These findings are supported by many other studies involving other populations around the world . On the other hand, sense of purpose in life was the major determinant of spiritual HRQOL after stroke.…”
Section: Discussionsupporting
confidence: 83%
“…Widely variable and sometimes contradictory socio‐demographic and clinical factors have been reported as possible determinants of post‐stroke HRQOL by researchers working with different populations . For instance, while post‐stroke emotional disorder was reported as a determinant of HRQOL in Melbourne , it was not assessed in a study of stroke patients in China .…”
Section: Introductionmentioning
confidence: 99%
“…Ten studies that could have potentially contributed to the review findings were excluded as authors were unavailable to provide necessary information. Reasons for exclusion were: reporting anxiety as a continuous outcome (23)(24)(25)(26), using a rating scale that measured anxiety but not reporting anxiety findings (27)(28)(29)(30), reporting only patients with comorbid anxiety and depression (31), reporting only correlations between anxiety and another variable (32), and an unpublished thesis that was not accessible (33). An updated search run in March 2011 found three additional studies, giving a total of 44 studies included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Another researcher showed that good social support and quality family assistance maintained, and in some cases even improved, the of the patients. (20,23) The presence of sequelae after stroke, generated dependence on the part of the patients for the performance of activities of daily living. In this study, 49.6% of patients had moderate to severe dependency, consistent with findings in the literature ranging between 31% and 62%.…”
Section: Discussionmentioning
confidence: 99%